2007
DOI: 10.1007/s11010-007-9650-z
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic acid and ascorbate prevent LDL oxidation and oxidant stress in endothelial cells

Abstract: Both alpha-lipoic acid (LA) and ascorbic acid (vitamin C) have been shown to improve endothelial dysfunction, a precursor of atherosclerosis. Since oxidant stress can cause endothelial dysfunction, we tested the interaction and efficacy of these antioxidants in preventing oxidant damage to lipids due to both intra- and extracellular oxidant stresses in EA.hy926 endothelial cells. LA spared intracellular ascorbate in culture and in response to an intracellular oxidant stress induced by the redox cycling agent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…Thus, it might be speculated that ALA might have influenced LDLcholesterol levels. Experimental and clinical studies have shown reduction of (oxidized) LDL by ALA [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be speculated that ALA might have influenced LDLcholesterol levels. Experimental and clinical studies have shown reduction of (oxidized) LDL by ALA [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Study has also shown that when proliferating endothelial cells were treated with AA, increased retinoblastoma protein (Rb) phosphorylation was observed with decreased level of p53 as compared to untreated cells. Furthermore, the addition of AA to TNF-alpha-treated proliferating endothelial cells blocked both the inhibition of retinoblastoma protein phosphorylation and enhanced p53 expression induced by TNF-alpha and TNF-alpha-induced apoptosis [117].…”
Section: Vitamin C and Atherosclerosismentioning
confidence: 92%
“…Further, lipophilic derivatives of AA showed protective effect on lipidperoxide induced endothelial injury [116]. In endothelial cells, AA prevented atherogenic modification of mildly oxidized LDL [110] and preserved a-tocopherol in both cells and LDL [117]. Although AA may not reverse established atherosclerosis, it can prevent the endothelial dysfunction that is the earliest sign of many vascular inflammatory conditions.…”
Section: Vitamin C and Atherosclerosismentioning
confidence: 99%
“…Glascott and co-workers (Glascott, Jr. et al, 1996) found that there was no sparing of α-tocopherol by ascorbate in hepatocytes exposed to an oxidant stress generated by allyl alcohol. On the other hand, subsequent studies in diverse cell types showed that ascorbate prevented α-tocopherol loss due to milder oxidant stresses in erythrocytes (May et al, 1998b), hepatocytes , and neuronal cells (Li et al, 2003) In endothelial cells, ascorbate prevented atherogenic modification of mildly oxidized LDL (Martin & Frei, 1997) and preserved α-tocopherol in both cells and LDL (Sabharwal & May, 2008). Despite results of in vitro studies, until recently it had not been demonstrated that ascorbate spares α-tocopherol in either animals or humans under oxidant stress.…”
Section: Ascorbate Dietary Requirements and Functionmentioning
confidence: 99%